Pengaruh Kecanduan Game Online terhadap Motivasi Belajar Siswa di SMP PKMI Methodist Aek Batu - Simanjuntak, Lestari Samantha; Siregar, Zunaidy Abdullah; Machrizal, Rusdi (Bioscientist : Jurnal Ilmiah Biologi, 2025)
This study aims to analyse the effect of online game addiction on students' learning motivation at SMP PKMI Methodist Aek Batu. This research uses a quantitative approach with survey method. The population consisted of 64 students, and the total sampling technique was used to determine the sample. The research instrument is a questionnaire that has been tested for validity and reliability. Data analysis was performed using Pearson's correlation test with IBM SPSS Statistics 23. The results of the study showed that there was no significant effect of online game addiction on student learning motivation, as evidenced by the correlation test results showing a significance value greater than 0.05 (> 0.05). This discrepancy in results may be influenced by factors such as time management, parental support, type of game, and the students' social environment. Therefore, it can be concluded that online gaming addiction does not directly affect students' learning motivation at SMP PKMI Methodist Aek Batu. Further research with a broader scope, larger sample size, and a mixed quantitative and qualitative approach is recommended to obtain more comprehensive results.